Computational Economics: rational behaviour and complexity - Gomes, Orlando (2018)
The central paradigm of analysis in Economics is based on the notion of representative agent. Inseparable from this notion is the idea of strict rationality, that is, the idea that economic agents possess an unlimited capacity to understand the reality that surrounds them, allowing them to formulate „correct‟ expectations about the future, i.e., expectations that at first do not incur in any error of a systematic nature. This view, although simplistic and reductionist in light of the true human behavior, has served for decades the purposes of economic science and allowed for important advances in what concerns the understanding of the reality that surrounds us. However, major reservations are posed today on the capacity of this paradigm to continue advancing the knowledge about the functioning of the economic system. The emergence of an interpretation of economics as a complex system is the recognition that different understandings of the concept of rationality are possible, that the economic agents are actually heterogeneous (in their actions, beliefs, expectations and preferences), and that these interact necessarily through a set of relationships in which learning, adaptation and evolution are central elements. In this paper, we review the recent literature on complexity in Economics and put in perspective thereafter the future of this science.